(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The COVID-19 pandemic has brought about a paradigm shift in the educational landscape, propelling the adoption of blended learning methodologies. This shift has necessitated a reassessment of research resources and the need for robust online research databases to support effective learning and teaching in a hybrid environment. Union Christian College (UCC) recognized this need and embarked on a project to establish an online research database to address the evolving demands of blended learning. Blended learning, which integrates traditional face-to-face instruction with online learning components, has emerged as a viable alternative to traditional brick-and-mortar education. The COVID-19 pandemic accelerated the adoption of blended learning as institutions sought to maintain educational continuity while adhering to social distancing measures. However, blended learning presents unique challenges in accessing and utilizing research resources. Traditional libraries and physical research repositories may not be readily accessible to students engaged in online learning components. UCC, recognizing the need for accessible research resources in a blended learning environment, the researchers undertook the development of an online research database to address these challenges and enhance the research and learning experience for its students and faculty. The database aims to provide a centralized repository of research materials, including academic journals, articles, and other relevant resources, in a readily accessible digital format. A set of operational concepts guided the design and implementation of the UCC online research database to ensure its effectiveness and alignment with the needs of blended learning. A comprehensive feasibility analysis was conducted to assess the viability of the UCC online research database project. The analysis considered technical, financial, stakeholder acceptance, institutional readiness, and long-term sustainability. Technical Feasibility: The technical feasibility assessment evaluated the availability of necessary ICT infrastructure, hardware, and software to support the database’s development and maintenance. Financial Feasibility: The financial feasibility assessment examined the costs associated with database development, maintenance, and ongoing resource acquisition to ensure the project’s financial sustainability. Stakeholder Acceptance: The stakeholder acceptance assessment gauged the level of support for the project among key stakeholders, including faculty, students, administrators, and librarians. Institutional Readiness: The institutional readiness assessment evaluated UCC’s organizational capacity and preparedness to undertake the project, including expertise, resources, and commitment from various departments. Long-Term Sustainability: The long-term sustainability assessment explored strategies for maintaining the database’s relevance, usefulness, and financial viability over an extended period. An effectiveness evaluation was conducted to assess the impact of UCC’s online research database on research collaboration, dissemination, and teaching and learning outcomes. The evaluation employed a mixed-methods approach, combining surveys, focus groups, and interviews with faculty and students. The evaluation yielded high validity ratings for the database’s effectiveness, with a grand mean of 4.66 on a 5-point scale. Respondents indicated that the database had significantly enhanced their access to research materials, facilitated research collaboration, and improved teaching and learning outcomes. Implications and Limitations The UCC online research database project highlights the significance of reliable research resources in supporting blended learning methodologies. The database’s effectiveness in enhancing research collaboration, dissemination, and teaching and learning outcomes underscores its value in the evolving educational landscape. However, the project also highlights the importance of addressing potential limitations. These include ensuring adequate ICT infrastructure, maintaining financial sustainability, fostering stakeholder engagement, and adapting to the ever-changing demands of blended learning. Recommendations for Future Directions The successful implementation of the UCC online research database project provides valuable insights for future directions in developing and utilizing research resources in blended learning environments.